THE INFLUENCE OF THE TREFFINGER LEARNING MODEL AND SELF-DIRECTED LEARNING ON STUDENTS’ MATHEMATIC CRITICAL THINKING SKILLS - Valeria Yekti Kwasaning Gusti; Wardani Rahayu (KALAMATIKA Jurnal Pendidikan Matematika, 2023)
The study investigated the influence of the Treffinger learning model and self-directed learning on the critical thinking skills of junior high school students. The Treffinger learning model is one of the few models addressing the problem of creativity and providing practical suggestions on how to achieve cohesion. On the other hand, self-directed learning is a mental process to increase the knowledge, skills, and self-achievement of individuals with self-planned and self-conducted activities. The research employed a post-test experiment and control group design with two groups. The study employed two groups; one group was treated using the Treffinger learning model, while the other group was treated using a conventional model. Both groups were analyzed using a self-directed learning questionnaire and a critical mathematical thinking skills test. The sample of this research comprised 88 Grade 8 students purposefully selected in relation to the research objectives. The results of the study showed that the Treffinger learning model was statistically significant in enhancing critical mathematical thinking skills compared to the conventional learning models. Additionally, the study found that students who exhibited high levels of self-directed learning were more likely to benefit from the Treffinger learning model than the conventional model, with a statistically significant mean difference of 3.05 points.